PENGARUH CELEBRITY CREDIBILITY TERHADAP BRAND ATTITUDE, ADVERTISEMENT ATTITUDE, DAN PURCHASE INTENTION - Daffa Danendra; Tarandhika Tantra (Value : Jurnal Manajemen dan Akuntansi, 2023)
MS Glow for Men, a skincare brand specifically for men, uses a celebrity endorser, Marshel Widianto, in its marketing. Her presence is a message to society, especially men, that they can take care of themselves. This strategy reaped a lot of negative comments from the people of Indonesia. the public feels that Marshel Widianto is inappropriate to represent the MS Glow for Men skincare brand because he does not have celebrity credibility or good enough credibility and does not meet beauty standard criteria as an endorser for care and beauty products. This study looks at the effect of celebrity credibility on purchase intention, brand attitude and advertisement attitude. This research is a quantitative study, with data collection by distributing questionnaires with a sample of 385 respondents and data analysis was carried out using the Covariant-Based Structural Equation Model with AMOS 24 software. The results showed that celebrity credibility has a significant effect on brand attitude, celebrity credibility has a significant effect on the advertisement attitude. However, it was found that celebrity credibility did not have a significant effect on purchase intention. Obtained advertisement attitude has a significant influence on purchase intention and brand attitude has a significant influence on purchase intention. Further research can add dimensions to the celebrity credibility variable, namely trustworthiness, attractiveness, and expertise to assess deeper celebrity credibility. Keywords: Credibility, Brand, Advertisement, Purchase